2007
DOI: 10.1039/b701012e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, coordination and catalytic use of 1-(diphenylphosphino)-1′-carbamoylferrocenes with pyridyl-containing N-substituents

Abstract: Ferrocene phosphinocarboxamides, 1-(diphenylphosphino)-1'-{N-[(2-pyridyl)methyl]carbamoyl}ferrocene (1) and 1-(diphenylphosphino)-1'-{N-[2-(2-pyridyl)ethyl]carbamoyl}ferrocene (2) were prepared from 1-(diphenylphosphino)-1'-ferrocenecarboxylic acid and studied as ligands for palladium. Starting with [PdCl2(cod)], the reactions at a 2 : 1 ligand-to-metal ratio gave uniformly the bis-phosphine complexes [PdCl2(L-kappaP)2] (3, L = 1; 4, L = 2) whereas those performed at a 1 : 1 ratio yielded distinct products: [P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…In both the silver center is found in a trigonal planar environment, with slightly distorted angles, the angles being for one of them N(4)eAg(1)eN(2) 91. 8(2), N(4)eAg(1)eP(1) 140.67 (18) and N(2)eAg(1)eP(1) 124.81(17) . The AgeN distances for one of the molecules are 2.291(7) and 2.327(7) Å and the AgeP is 2.365(2), which are similar to those found in three coordinated silver(I) complexes such as [Ag 2 {3,5e(CF 2 ) 2 CF 3 etriaz} 2 (PPh 3 ) 2 ] [31].…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…In both the silver center is found in a trigonal planar environment, with slightly distorted angles, the angles being for one of them N(4)eAg(1)eN(2) 91. 8(2), N(4)eAg(1)eP(1) 140.67 (18) and N(2)eAg(1)eP(1) 124.81(17) . The AgeN distances for one of the molecules are 2.291(7) and 2.327(7) Å and the AgeP is 2.365(2), which are similar to those found in three coordinated silver(I) complexes such as [Ag 2 {3,5e(CF 2 ) 2 CF 3 etriaz} 2 (PPh 3 ) 2 ] [31].…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…Ferrocenyl derived phosphines have been accessed through a number of established methods previously [1a, 2,6,8,12,14]. In our work we have found that phosphorus based Mannich condensation reactions are extremely flexible procedures for preparing highly functionalised phosphines [41] and even nonsymmetric diphosphines [42] by employing two consecutive elimination steps.…”
Section: Ligand Synthesismentioning
confidence: 99%
“…The versatility of the Fc group in synthesis can be illustrated by some of the diverse compounds (Chart 1) previously documented in the literature. The Fc group can be employed either as a substituent bonded to phosphorus [6] or a metal centre [7] through an ethynyl linker or alternatively as a backbone for accessing primary and secondary phosphines [8], di-and polyphosphines [9,10], nonsymmetric ligands [11][12][13][14] and chiral systems [15][16][17][18]. To date, 1,1 0 -bis(diphenylphosphino)ferrocene (dppf) possibly remains the most iconic example of a phosphorus(III) based ligand containing the Fc moiety [4,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Neutral P , N , P ‐ligands based on a central pyridine unit are currently attracting great interest as versatile non‐innocent scaffolds for homogeneous catalysis 31. Compound 4 was synthesised in analogy to 1 by Negishi cross‐coupling of Ph 2 PfcZnCl with 2,6‐dibromopyridine 4a. It was structurally characterised by single‐crystal X‐ray diffraction analysis (Figure 7).…”
Section: Resultsmentioning
confidence: 99%